A 5-Year Audit of Accidental Dural Punctures, Postdural Puncture Headaches, and Failed Regional Anesthetics at a Tertiary-Care Medical Center - Sukhdip Singh; Shagufta Y. Chaudry; Amy L. Phelps; Manuel C Vallejo (The Scientific World Journal)
Obstetric anesthesia-related complications occur as a result of labor epidural or spinal placement. The purpose of this continuous quality-improvement audit was to review the occurrence of accidental dural punctures (ADPs), postdural puncture headaches (PDPHs), and failed regional anesthetics at an academic tertiary-care medical center over a 5-year period. Obstetric anesthesia complications contained in three databases consisting of ADPs, PDPHs, and failed regional anesthetics were matched to a perinatal database, with no complications serving as controls. Of the 40,894 consecutive parturients, there were 765 documented complications. Complication rates were 0.73% (95% CI: 0.65–0.82) for ADP, 0.49% (95% CI: 0.43–0.56) for PDPH, and 0.65% (95% CI: 0.57–0.73) for failed regional anesthetic. When compared to the no complication group, factors associated with obstetric anesthesia complications included increased weight and BMI (p < 0.01), epidural block (p < 0.01), and vaginal delivery (p< 0.01).